Lacasse Catalyzed-Synthesis of 4,4?-Biphenyldiamine from P-Chloroaniline. Evaluation of Antifungal and Antioxidant Activities - Cotoras-Tadic, M; Campos-Deramond, A; Campos-Deramond, A; Mendoza-Espinola, L; Mendoza-Espinola, L (Sociedad Chilena de Quimica, 2016)
Laccase is a copper-containing oxidase that catalyzes reduction of molecular oxygen to water and the oxidation of a phenolic compound. In this paper, laccase was utilized to synthesize 4,4′-Biphenyldiamine using p-chloroaniline as substrate by means of a coupling reaction. The synthesized compound, 4,4′-Biphenyldiamine, presented low antifungal activity against the phytopathogenic fungus Botrytis cinerea, however the antioxidant ability, measurement by ORAC-PGR method, was higher than substrate. This work corresponds to the first report of synthesis 4,4′-Biphenyldiamine, from p-chloroaniline in a lacasse-catalyzed reaction. © 2016, Sociedad Chilena de Quimica. All rights reserved.